2014
DOI: 10.1007/s11199-014-0348-x
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Among Women with HIV: Impact of Silencing the Self and Socioeconomic Factors

Abstract: In the U.S., women account for over a quarter of the approximately 50,000 annual new HIV diagnoses and face intersecting and ubiquitous adversities including gender inequities, sexism, poverty, violence, and limited access to quality education and employment. Women are also subjected to prescribed gender roles such as silencing their needs in interpersonal relationships, which may lessen their ability to be resilient and function adaptively following adversity. Previous studies have often highlighted the strug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 62 publications
2
65
0
5
Order By: Relevance
“…If protective factors outnumber risk factors (factors increasing the possibility of incompatible outcomes), it is predicted that the individual, in dealing with problems, displays more resilient behavior, copes with problems, and does not experience mental health disorders (22,65). Self-efficacy, social support, occupation, higher education, self-esteem, positive social orientation, asking for help, stress management, locus of control, coping, and older age are the most important protective factors that play a key role in the demonstration of compatible behavior and protection of mental health in difficult situations (66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…If protective factors outnumber risk factors (factors increasing the possibility of incompatible outcomes), it is predicted that the individual, in dealing with problems, displays more resilient behavior, copes with problems, and does not experience mental health disorders (22,65). Self-efficacy, social support, occupation, higher education, self-esteem, positive social orientation, asking for help, stress management, locus of control, coping, and older age are the most important protective factors that play a key role in the demonstration of compatible behavior and protection of mental health in difficult situations (66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: Discussionmentioning
confidence: 99%
“…As regards sex, age group, education level, income, and current employment situation, no significant differences were found among patients. However, a recent study revealed that HIV-positive women with a low education level, low income, and no employment had high levels of resilience (Dale et al, 2014). Another previous study on asymptomatic seropositive men with low income and low education level showed that they had low levels of resilience (Lima et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…As regards the link between resilience and sociodemographic variables, it has been shown that HIVpositive women with low education levels, low income, and no employment had high levels of resilience (Dale et al, 2014). Other studies have concluded that resilience was lower among asymptomatic seropositive males with lower levels of education and limited economic means (Lima, Azevedo, Amorim, & Saldanha, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Resiliensi seperti sebuah lintasan peluru yang dapat berpengaruh terhadap banyak hal, seperti: peningkatan kualitas kesehatan mental dan atau mengurangi gejala penyakit fisik tertentu. Hasil yang diperoleh pun berbeda-beda di tiap wilayah, sehingga faktor kebudayaan dan agama menjadi salah satu penentu kemampuan resiliensi individu (Dale, Cohen, Kelso, Cruise, Weber, Watson, Brody, 2014).…”
Section: │ 137unclassified
“…Literasi penelitian terdahulu menganalogikan resiliensi seperti proses melentingnya bola bekel. Proses tersebut merupakan perumpamaan bagi individu yang terpuruk namun mampu bangkit kembali ke kondisi psikologis sebelum menghadapi kemalangan (Dale et al, 2014).…”
Section: │ 137unclassified